ANALISIS PENERAPAN SISTEM DAN PROSEDUR PENERIMAAN DAN PENGELUARAN KAS PADA PERUSAHAAN UMUM DAERAH PASAR KOTA KENDARI - Fitria Desy; Ishak Awaluddin; Tuti Dharmawati (Jurusan Akuntansi, Universitas Halu Oleo, 2026)
This study aims to analyze the implementation of cash receipt and cash disbursement systems and procedures at the Perusahaan Umum Daerah Pasar Kota Kendari. The accounting system plays an important role in supporting the effectiveness of financial management due to the high intensity of cash receipt and cash disbursement transactions in operational activities. This research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The research findings indicate that the cash receipt system is still implemented using conventional methods, specifically cash-based payments for market management retribution activities. This condition potentially leads to delays in financial reporting and fund misappropriation, resulting in discrepancies between physical cash on hand and the actual amounts deposited, as well as weak segregation of duties between cash receiving and recording functions. Meanwhile, the cash disbursement procedures have not been fully conducted through strict authorization mechanisms, and internal control has not been implemented optimally. Although the cash receipt and disbursement systems and procedures have been established, their implementation has not yet fully complied with standard operating procedures and the applicable regulations.